Normal people scare me [videorecording (DVD)] - Travolta, Joey; Cross, Taylor; Nash, Graham. 1942-; Dayne, Taylor (Normal Films, 2006)
17- year old Taylor Cross captures life and living with autism through interviews with over 65 subjects who have either Asperger's syndrome or autism. Originally a 10-minute short made in 2004 for a high school class, Taylor and his co-director (and mom) took his short as a starting point for this longer feature which looks at the attention the short film brought to him and autism, and enlarges on the subject of what living with autism & Asperger's means.